Writing for Wellness: A Literature Review on the Effectiveness of Expressive Writing on the Mental Health of Cancer Patients and Cancer Survivors - Lovina Jayanti (International Journal of Public Health, 2025)
Cancer is a chronic disease that not only affects physical conditions but also imposes a significant psychological burden on both cancer patients and cancer survivors. Various mental health problems, such as anxiety, depression, stress, and psychological distress, are frequently experienced throughout the processes of diagnosis, treatment, and the survivorship phase. One psychological intervention that has developed and been widely studied is expressive writing, which allows individuals to freely express their thoughts and emotions through writing. This study aims to examine the effectiveness of expressive writing interventions on the mental health of cancer patients and cancer survivors using a literature review method. The article search process was conducted in international databases (ScienceDirect, PubMed, and SpringerLink) and a national database (Garuda), covering publications from 2020 to 2025. Article selection was carried out using PRISMA guidelines, and methodological quality assessment was conducted using the Critical Appraisal tools from the Joanna Briggs Institute (JBI). Based on the selection results, nine articles met the eligibility criteria for analysis. The review findings indicate that most studies report positive effects of expressive writing in reducing anxiety, depression, stress, and psychological distress, as well as improving quality of life, positive affect, self-efficacy, and posttraumatic growth. However, the effectiveness of this intervention varies depending on individual characteristics, clinical context, writing structure and focus, intervention duration, and cultural appropriateness. Therefore, expressive writing has the potential to serve as an effective, flexible, and low-cost supportive intervention in cancer care, particularly when it is designed contextually and adaptively in accordance with patients’ psychological needs.